SPEAKING ENGLISH IN THE PESANTREN: A GENDER-BASED ANALYSIS OF MORPHOSYNTACTIC AND LEXICAL PATTERNS - Tanzir Masykar; Mahlil Mahlil; Hery Wiharja; Febri Nurrahmi; Nurul Taflihati Masykar; Riza Hasan (Indonesian EFL Journal, 2025)
English has become a significant medium of communication in Indonesian pesantren, yet limited research has examined how students in this setting produce spoken English. Previous studies have largely focused on curriculum, teacher identity, and learner motivation, while little attention has been given to the morphosyntactic and lexical features of pesantren students’ actual speech. This study addresses the gap by analyzing the spoken English of 19 students (10 male, 9 female) from a pesantren in Banda Aceh through recorded interviews that were transcribed and coded for grammatical, lexical, and discourse errors. Error types were classified using an SLA-oriented framework, including inflectional and derivational morphology, syntax, lexical choice, pragmatic/discourse, and interlingual errors. The findings reveal that female students were more vulnerable to inflectional morphology errors (50.72%), particularly with verb tense, copula omission, articles, and plural –s. Male students showed higher proportions of syntax errors (33.88%) and pragmatic/discourse errors (7.10%), including misordering, fragments, redundancy, and repetition. Both groups shared difficulties with derivational morphology and lexical choice, while interlingual interference was minimal. The results suggest that while pesantren students share developmental L2 difficulties, gender-based differences emerge in their grammatical and discourse patterns, offering implications for pedagogy and curriculum design.